A light in the dark: state of the art and perspectives in optogenetics and optopharmacology for restoring vision. (25th March 2019) - Chemi, Giulia; Brindisi, Margherita; Brogi, Simone; Relitti, Nicola; Butini, Stefania; Gemma, Sandra; Campiani, Giuseppe
In the last decade, innovative therapeutic strategies against inherited retinal degenerations (IRDs) have emerged. In particular, chemical- and opto-genetics approaches or a combination of them have been identified for modulating neuronal/optical activity in order to restore vision in blinding diseases. The 'chemical-genetics approach' (optopharmacology) uses small molecules (exogenous photoswitches) for restoring light sensitivity by activating ion channels. The 'opto-genetics approach' employs light-activated photosensitive proteins (exogenous opsins), introduced by viral vectors in injured tissues, to restore light response. These approaches offer control of neuronal activities with spatial precision and limited invasiveness, although with some drawbacks. Currently, a combined therapeutic strategy (optogenetic pharmacology) is emerging. This review describes the state of the art and provides an overview of the future perspectives in vision restoration. Graphical abstract: